EVALUATING LESSON PLAN OF LISTENING COMPREHENSION - Leni Irianti (BRIGHT : A Journal of English Language Teaching, Linguistics and Literature, 2019)
In Listening class the learner are demanded to be a critical thinker who can identify something explicitly stated in spoken text. Identifying the main idea means the students were able to engage the studentsâ€™ in listening, such as they are able distinguishing the main idea from supporting details, distinguishing fact, example, and opinion. This study aims at examining the lesson plan of listening especially in identifying the main idea in spoken text, whether the lesson plan has fulfill the indicators of understanding main idea in spoken text or not. This study also attempts to analyze the studentsâ€™ feedback to the lesson plan regarding to their learning improvement. Thus, this study also identifies the gap between the lesson plan and the impact toward the studentsâ€™ performance in listening. The researcher uses a survey checklist focusing on the key elements of the self-evaluation of a teacherâ€™s lesson and questionnaire for studentsâ€™ appraisal. Their responses are analyzed by using a document analysis and questionnaire description. Based on data analysis, the present lesson plan meets out its objectives to certain point but not completely. The result shows that most of the statements based on the key elements of the lesson plan fall into the category of â€œmoderateâ€ it is suggested that the lesson plan should be revised so that it fulfills the objectives of the course completely. Considering the studentsâ€™ course evaluation the lesson should be updated.